Safety of Prolonged Inhalation of Hydrogen Gas in Air in Healthy Adults - Alexis R. Cole, BS (Wolters Kluwer, 2021)
BACKGROUND:. Ischemia-reperfusion injury is common in critically ill patients, and directed therapies are lacking. Inhaled hydrogen gas diminishes ischemia-reperfusion injury in models of shock, stroke, and cardiac arrest. The purpose of this study was to investigate the safety of inhaled hydrogen gas at doses required for a clinical efficacy study. DESIGN:. Prospective, single-arm study. SETTING:. Tertiary care hospital. PATIENTS/SUBJECTS:. Eight healthy adult participants. INTERVENTIONS:. Subjects underwent hospitalized exposure to 2.4% hydrogen gas in medical air via high-flow nasal cannula (15 L/min) for 24 (n = 2), 48 (n = 2), or 72 (n = 4) hours. MEASUREMENTS AND MAIN RESULTS:. Endpoints included vital signs, patient- and nurse-reported signs and symptoms (stratified according to clinical significance), pulmonary function testing, 12-lead electrocardiogram, mini-mental state examinations, neurologic examination, and serologic testing prior to and following exposure. All adverse events were verified by two clinicians external to the study team and an external Data and Safety Monitoring Board. All eight participants (18–30 yr; 50% female; 62% non-Caucasian) completed the study without early termination. No clinically significant adverse events occurred in any patient. Compared with baseline measures, there were no clinically significant changes over time in vital signs, pulmonary function testing results, Mini-Mental State Examination scores, neurologic examination findings, electrocardiogram measurements, or serologic tests for hematologic (except for clinically insignificant increases in hematocrit and platelet counts), renal, hepatic, pancreatic, or cardiac injury associated with hydrogen gas inhalation. CONCLUSIONS:. Inhalation of 2.4% hydrogen gas does not appear to cause clinically significant adverse effects in healthy adults. Although these data suggest that inhaled hydrogen gas may be well tolerated, future studies need to be powered to further evaluate safety. These data will be foundational to future interventional studies of inhaled hydrogen gas in injury states, including following cardiac arrest.